(untitled) (Revista Contexto & Educação, 2026)
In the face of the current environmental and civilizational crisis, it is urgent to rethink teacher education processes by overcoming conservative and fragmented approaches. In this context, critical Environmental Education (EE), grounded in the thought of Paulo Freire, proposes dialogical, emancipatory practices committed to social transformation. This study analyzed the meanings attributed to transformative EE by participants in a training process guided by Freirean pedagogy. The research has a qualitative and exploratory nature and was conducted with participants of the First Continuing Education Course in Environmental Education in the surroundings of Iguaçu National Park, Brazil. The course took place in 2025 and was offered in hybrid and virtual modalities. In the hybrid format, the target audience consisted of teachers and students from municipalities surrounding Iguaçu National Park, while the virtual modality allowed the participation of individuals from different regions of the country. Data were collected through a questionnaire administered after one of the training meetings, including an open-ended question on how EE can overcome isolated awareness-raising practices and promote transformative action. The questionnaire received 36 responses, which were analyzed according to the principles of Content Analysis. The meanings attributed to transformative EE indicate an understanding of its critical, dialogical, and emancipatory principles. Transformative action was associated with the formation of critical subjects capable of understanding the structural causes of the socio-environmental crisis, participating in collective decision-making processes, and acting toward the promotion of socio-environmental justice. These results indicate the formative potential of the course to foster critical reflection on educational practice.